Actual and Declared Attitudes Towards Financial Risk among Students of the University of Warmia and Mazury in Olsztyn - Brzezicka, Justyna; Pirożek, Katarzyna; Grabowski, Paweł (Olsztyn Economic Journal, 2024)
The article is dedicated to the issue of actual and declared attitudes toward risk among students of the University of Warmia and Mazury in Olsztyn. The research was carried out using a survey (100 questionnaires) in December 2022 as an extension of the work carried out by the students in their thesis. The survey asked respondents to identify their self-reported attitude towards risk (risk averse, risk seeker, risk neutral attitude) and then assessed their actual attitude towards risk using the certainty equivalent method, known from behavioral economics. The study had specific objectives to identify risk attitudes among students and to identify differences between their actual and declared risk attitudes. The most significant conclusions of the study are as follows. Students are not aware of their own attitudes towards risk - only about 30% of the survey sample shows a match between actual and declared attitudes. According to the actual data, risk averters respondents are 41%, those with a risk-neutral attitude 21% and risk-seekers 38%. In the case of the declared data it was respectively: 50%, 6% and 34%.